2007
DOI: 10.1108/07363760710834843
|View full text |Cite
|
Sign up to set email alerts
|

Firms' complaint handling policies and consumer complaint voicing

Abstract: PurposeThe purpose of this research is to examine the effects of actions recommended by researchers for firms to encourage complaint voicing, and test the proposition that complaining by dissatisfied consumers would increase if only firms would make it easier to complain.Design/methodology/approachAn experimental study assessed consumer reactions to scenarios in which a retailer made it easier or harder to complain by varying its refund policy, employee empowerment, access to call center representatives, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 38 publications
2
46
0
9
Order By: Relevance
“…In such cases, dissatisfied customers are more likely to voice their complaints to the service provider than complain to others. This finding is consistent with those of Huppertz (2007), who found that a firm's complaint policy and subsequent actions effectively lead to expectations of service recovery.…”
Section: H9supporting
confidence: 93%
“…In such cases, dissatisfied customers are more likely to voice their complaints to the service provider than complain to others. This finding is consistent with those of Huppertz (2007), who found that a firm's complaint policy and subsequent actions effectively lead to expectations of service recovery.…”
Section: H9supporting
confidence: 93%
“…Customer"s reaction to service failure is affected by many factors such as level of dissatisfaction (Mittal, Huppertz, & Khare, 2008), the likelihood of service recovery (Blodget & Granbois, 1992), the ease of process of complaining (Blodget & Anderson, 2000), and the perception that whether or not company will respond back (Huppertz, 2007). Other factors may include current relationship of consumer with the company (Hui, Ho, & Wan, 2011) and consumer"s attitude toward complaining (Kim, Kim, Im, & Shin, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of companies support most of the mentioned communication channels and customers have general channel preferences, the implementation, execution, and supervision of each channel affects customers' satisfaction levels (Blodgett et al 1995). These attributes can be consolidated as a major part of a company's complaint management policy (Huppertz 2007). Section 2.4 highlights the major determinants of customer satisfaction in complaint management policies, which are essential for the conceptualisation in Chap.…”
Section: Typology Of Communication Channelsmentioning
confidence: 99%